Public Beliefs In The Brendung Ritual To Call Rain In Gutomo Village, Karanganyar Kajen District - Atiyatul Karima; Elita Rahma, Aqila (IQTIDA : Journal of Da'wah and Communication, 2024)
This research discusses a belief among the people of Gutomo Village, Karanganyar Kajen District, namely the brendung ritual to summon rain. This research is a socio-cultural study that occurred in the Gutomo Village community, Karanganyar Kajen District. A rain charmer is someone who has the advantage of summoning rain in the dry season among the people of Gutomo Village, Karanganyar Kajen District to this day. Apart from being a belief, the brendung ritual is used as entertainment and a form of cultural heritage. The theory used is the sacred and profane theory according to Emile Durkheim. This research uses an ethnographic method which produces descriptive qualitative data The result of this research is that there is a change in people's beliefs towards the brendung ritual. Originally this belief was considered a ritual to summon rain and was full of mystical content. However, even though it is still embedded as cultural heritage, this ritual is also used as entertainment during the dry season.